Technology-based classroom management optimization for learning effectiveness in madrasah - M Sahrawi Saimima; N Thati Kaplale; Kapraja Sangadji; Adam Jait (12 Waiheru, 2026)
The paper in this study aims to analyze the implementation of classroom management to improve learning effectiveness at Madrasah Ibtidaiyah Terpadu (MIT) As Salam Ambon, and to examine the application of management functions in technology-based classroom management. This research uses a qualitative, descriptive approach. The research subjects were teachers directly involved in the learning process, selected through purposive sampling. Data collection is conducted through in-depth interviews, observations, and documentation, while data analysis uses an interactive model across the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that classroom management is implemented systematically through four management functions: planning, organizing, implementing, and controlling. In the planning stage, Teachers develop learning tools that are integrated with technology and adapted to the needs of students, such as the use of smart TVs in presenting teaching materials, then using digital worksheets equipped with YouTube video inserts or audio explanations of the material in the worksheet, then also using applications such as Quizizz. In the organizing stage, teachers manage the classroom effectively by arranging the class structure, dividing groups, and using technology-based learning resources. In the implementation stage, learning takes place in an interactive, varied manner, with the support of digital media that encourages student involvement. Meanwhile, at the control stage, evaluation is carried out on an ongoing basis through formative and summative assessments followed by learning follow-up. Thus, the research findings show that integrating technology into classroom management significantly increases learning effectiveness, as reflected in increased student motivation, participation, and learning outcomes.